A multilevel approach to the path to expertise in three different competitive settings - Gonçalves, Carlos Eduardo (2014)
The objectives of the study were to analyze the deliberate practice variables in three different youth competitive sport settings; to analyze the effects of a season-long exposure on deliberate practice variables. The study explores three contexts in two different sports, soccer and volleyball, and at two competitive levels. The athletes fulfilled the questionnaire at the beginning and at the end of the season. A multilevel analysis was performed. Forty eight boys aged 15-17 years (14 from a volleyball club; 14 from an elite volleyball centre; 20 from a professional soccer club) participated in the study. The measure was an adapted version for soccer and volleyball of the Deliberate Practice Motivation Questionnaire, which assesses two dimensions: the will to compete and the will to excel. Fewer people in the volleyball group showed a will to excel, the soccer group showed an increase in the scores. In will to compete, the three teams showed a decrease in their means. The decrease is more pronounced in the will to excel but the context effect is not significant. The biggest decrease is shown by the elite volleyball team, followed by the club teams. The findings raise questions for managers and coaches who look for physical and technical gifted young athletes and aim to develop their qualities through a careful planned training programme. The insertion in programmes that are believed to foster expertise seems to have unexpected consequences. Sport participation cannot rely exclusively on an orientation toward expertise, forgetting the autonomy of young people to set their goals.